2021
DOI: 10.3390/app11020474
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Changes in Composite Materials during Photopolymerization

Abstract: During polymerization, composite materials cause a temperature rise which may lead to irreversible changes in the dental pulp. The mechanical properties of composite materials depend on a number of factors, such as the composition of the material, the type of polymerization unit, the polymerization mode, and the duration of polymerization. The objective of this study was to assess the temperature rise values and flexural strength of composite materials, as obtained using different modes and times of polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…An acrylic resin matrix was used to apply the resin composites. When one exposure time was used (5, 10 s), they found that the continuous mode and pulse mode produced similar temperature rise values (14, 15.5℃ respectively) [40]. These results do not agree with those of our study, which may be because that study neglected the effect of dentin on temperature rise.…”
Section: Discussioncontrasting
confidence: 84%
“…An acrylic resin matrix was used to apply the resin composites. When one exposure time was used (5, 10 s), they found that the continuous mode and pulse mode produced similar temperature rise values (14, 15.5℃ respectively) [40]. These results do not agree with those of our study, which may be because that study neglected the effect of dentin on temperature rise.…”
Section: Discussioncontrasting
confidence: 84%
“…Szalewski et al 40 measured the temperatures following polymerization of resin composites with seven curing modes (four continuous modes with exposure times of 3-5-10 and 20 s, two pulse modes with exposure times of 5 and 10 s, and soft-start mode). an acrylic resin matrix was used to apply the resin composites.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation systems and translucency properties of bulk-fill composites (BFC) promise an increased depth of cure. Extended polymerization durations are more likely to lead to the critical temperature values for pulp damage than short polymerization durations, suggesting that the use of bulk-fill composites in the restoration of deep Class II cavities is advantageous to preserve pulp health [ 9 ]. Stress-reliever technologies result in the reduction of polymerization shrinkage stresses.…”
Section: Introductionmentioning
confidence: 99%